From Foes to Friends: The Normalization of the United Emirates Arab and Israel Relations - Ahmad Mudhofarul Baqi (Insignia: Journal of International Relations, 2022)
Abstract This article aims to explain the reason the United Arab Emirates (UAE) normalized ties within Israel through Abraham Accord. The normalization of the UAE-Israel ties contra with the position of UAE as a part of the members of Gulf Cooperation Council (GCC) and Arab League that have long been conflicting within Israel, due to Israel's annexation over Palestinians. Utilize explanative type and constructivism paradigm based on identity as a tool of analysis, and supported with the secondary data. This article found the difference in religious identity, not automatic interfere step of UAE and Israel normalization process. The normalization of the UAE and Israel drive by the threat of Iran in the region. The threat shape collective identity between UAE and Israel as friends and Iran as a common enemy. The collective identity was also constructed via systemic processes in the form of interdependency and proximity with the United States of America. The collective identity was also constructed through strategic practice by both leaders. Furthermore, amongst UAE and Israel gathered through a type of identity Abraham's religion. Keyword: Normalization, UAE, Israel, Identity, Iran, and Constructivism Abstrak Artikel ini bertujuan untuk menjelaskan alasan Uni Emirat Arab (UAE) menjalin normalisasi hubungan dengan Israel melalui perjanjian Abraham Accord. Normalisasi hubungan UAE dengan Israel kontras dengan posisi UAE sebagai negara teluk (GCC) dan Liga Arab yang telah lama berkonflik dengan Israel atas aksi aneksasi Israel di wilayah Palestina. Menggunakan jenis penelitian eksplanatif dengan paradigma konstruktivisme berbasis identitas sebagai pisau analisis, serta didukung oleh data sekunder. Artikel ini menemukan bahwa perbedaan identitas agama tidak lantas menyurutkan langkah UAE dan Israel melakukan normalisasi hubungan. Israel-UAE normalization didorong oleh konteks ancaman regional berupa agresivitas Iran di kawasan. Konteks ancaman Iran membentuk collective identity antara UAE dan Israel sebagai sahabat dan Iran sebagai musuh bersama. Collective identity juga tercipta melalui proses sistemik berupa interdependensi UAE dan Israel dan kedekatan keduanya dengan Amerika Serikat. Collective identity juga terbentuk lewat praktik strategis kedekatan pemimpin kedua negara. Selain itu, antara UAE dan Israel juga disatukan lewat identitas tipe agama Abraham. Kata kunci: Normalisasi, UAE, Israel, Identitas, Iran, dan Konstruktivisme